2004
DOI: 10.1111/j.1523-1755.2004.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Actin cytoskeleton in ischemic acute renal failure

Abstract: CASE PRESENTATIONA 36-year-old African American man was evaluated in the emergency room at Wishard Memorial Hospital following a motor vehicle accident. The patient's car was hit from behind, and as he fled the scene of the accident, he fell and rolled down a hill. He was subsequently detained by police and brought to the hospital for evaluation of diffuse trauma and myalgias. In the emergency room, he was awake and alert but tachycardic, with a heart rate of 136 beats/min, a respiratory rate of 20 breaths/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 98 publications
1
50
0
3
Order By: Relevance
“…Along with this hypothesis, spe- cific PPAR␤ ligands have been shown to inhibit the expression of proinflammatory cytokines (e.g., monocyte chemoattractant protein-1) in both macrophages and endothelial cells (27,28). Because vascular endothelium activation and injury contribute to reduce renal perfusion and, hence, to decrease GFR (29,30), PPAR␤ ligands would protect renal function by preventing these mechanisms as well.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this hypothesis, spe- cific PPAR␤ ligands have been shown to inhibit the expression of proinflammatory cytokines (e.g., monocyte chemoattractant protein-1) in both macrophages and endothelial cells (27,28). Because vascular endothelium activation and injury contribute to reduce renal perfusion and, hence, to decrease GFR (29,30), PPAR␤ ligands would protect renal function by preventing these mechanisms as well.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the duration of ischemia results in worse cell injury, reduced function, and longer recovery periods (42,43). Pioneering work in rats using the renal artery clamp model revealed that PTCs recovered rapidly and completely following mild ischemia via cellular repair.…”
Section: Proximal Tubule Cellsmentioning
confidence: 99%
“…16 These changes occur very rapidly, correlate with the severity and duration of experimental AKI, and are important for the structural and functional integrity of renal proximal tubule cells, endothelial cells, and vascular smooth muscle cells during AKI. Alterations in the actin cytoskeleton regulate changes in cell polarity, cell-cell interactions, and cell-matrix interactions, and, as a result, influence the GFR and tubular function.…”
Section: Cytoskeletonmentioning
confidence: 99%